Psychometric Properties of a Chatbot Version of the PHQ-9 With Adults and Older Adults - Gilly Dosovitsky; Erick Kim; Eduardo L. Bunge (Frontiers Media S.A., 2021)
Background: The Patient Health Questionnaire-9 (PHQ-9) is a brief depression measure that has been validated. A chatbot version of the PHQ-9 would allow the assessment of depressive symptoms remotely, at a large scale and low cost.Objective: The current study aims to: Assess the feasibility of administering the PHQ-9 in a sample of adults and older adults via chatbot, report the psychometric properties of and identify the relationship between demographic variables and PHQ-9 total scores.Methods: A sample of 3,902 adults and older adults in the US and Canada were recruited through Facebook from August 2019 to February 2020 to complete the PHQ-9 using a chatbot.Results: A total of 3,895 (99.82%) completed the PHQ-9 successfully. The internal consistency of the PHQ-9 was 0.896 (p < 0.05). A one factor structure was found to have good model fit [X2 (27, N = 1,948) = 365.396, p < 0.001; RMSEA = 0.080 (90% CI: 0.073, 0.088); CFI and TLI were 0.925 and 0.900, respectively, and SRMR was 0.039]. All of the demographic characteristics in this study were found to significantly predict PHQ-9 total score, however; their effect was negligible to weak.Conclusions: There was a large sample of adults and older adults were open to completing assessments via chatbot including those over 75. The psychometric properties of the chatbot version of the PHQ-9 provide initial support to the utilization of this assessment method.